Learning Apple OS X Yosemite Server - Tarnowieckyi, Chris (Infinite Skills, 2015)
"In this Learning Apple OS X Yosemite Server training course, expert author Chris Tarnowieckyi will teach you how to install, upgrade, and configure a Server. This course is designed for beginning and intermediate Mac users who are looking to learn about the Yosemite Server. You will start with an introduction to the Server app, then jump into learning about advanced tools and management. From there, Chris will teach you about network infrastructure services, how to secure services with certificates, and basic directory services. This video tutorial also covers topics such as open directory, mobile device management, managing updates and apps, configuring the time machine, and file sharing. You will also learn about the mail server, web server, wiki server, and contacts server. Finally, you will learn how to configure the NetInstall service, as well as the Xcode service."--Resource description page.